Simple And New Tuning Method For Fuzzy PI Controllers For A Tape Transport System - Lee, Wah Soon (2007)
In this thesis, it is demonstrated that a properly tuned fuzzy PI Controller is able to reduce coupling effects between loops of a MIMO system, and it is also performing well even though the dynamics of a system have changed.